EVALUATİON OF NATURAL STOCKS OF MEDİCİNAL LEECHES İN WETLAND ECOSYSTEMS AND SUSTAİNABLE MANAGEMENT RECOMMENDATİONS - Mustafa Ergun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
Medicinal leeches, particularly Hirudo verbana, are recognized as sensitive bioindicators of freshwater ecosystems, and water quality parameters directly govern their entire life cycle. Key physicochemical variables such as temperature, dissolved oxygen concentration, pH, electrical conductivity, and organic matter load constitute the primary environmental determinants regulating metabolic activity, growth performance, and survival rates. Optimal thermal regimes and sufficient dissolved oxygen levels enhance post-feeding digestion efficiency, accelerate somatic growth, and improve overall physiological condition. Conversely, contamination by heavy metals, pesticides, and surfactants exerts both acute and chronic toxic effects, disrupting osmoregulatory balance, suppressing immune function, and elevating oxidative stress. These stressors may result in reduced hematophagous activity, impaired growth trajectories, increased mortality, and diminished reproductive fitness. Water quality also plays a decisive role in reproductive success and cocoon production. Under suitable environmental conditions, medicinal leeches exhibit higher cocoon output, increased hatchling numbers per cocoon, and improved embryonic development rates. In contrast, suboptimal water quality may lead to structural abnormalities in cocoon morphology, decreased hatching success, and prolonged incubation periods. Therefore, the conservation of natural populations and the sustainability of aquaculture-based production systems depend fundamentally on systematic monitoring of water quality parameters and the implementation of ecosystem-based management strategies. Such an integrative approach is essential not only for maintaining biodiversity integrity but also for ensuring the long-term continuity of medicinal leech resources for therapeutic applications. This study was designed as a comprehensive review aiming to evaluate the effects of water quality on the life cycle, physiological processes, reproductive success, and sustainability of medicinal leeches, particularly Hirudo verbana. Within the scope of the study, the critical role of water quality in both natural habitats and aquaculture systems was examined through a holistic assessment of national and international scientific literature. In particular, the effects of major water quality parameters, including temperature, dissolved oxygen, pH, organic load, and nitrogenous compounds, on growth performance, behavioral characteristics, population dynamics, and ecological tolerance of medicinal leeches were comparatively evaluated. Furthermore, the ecological significance of medicinal leeches as bioindicator organisms in freshwater ecosystems was emphasized, highlighting that preserving water quality is essential not only for the continuity of natural populations but also for the development of sustainable aquaculture practices